2019
DOI: 10.1039/c8ra08451c
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of AOS–iron on iron deficiency anemia in rats

Abstract: Iron deficiency anemia (IDA) is one of the most serious nutritional problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 57 publications
11
12
1
Order By: Relevance
“…1B showed histopathological alterations in the liver, dilatation of both central and portal veins, distension and hemorrhage in the central vein, loss of the normal hepatocytes architecture, degenerated hepatocytes with pyknotic nuclei, hepatocyte vacuolization, dilation and activation of Kupffer cells of hepatic sinusoids, and the aggregation of lymphocytes. Similar results for normal and anemic livers were reported by He et al 46 The differences in hepatic sinusoids and hepatic plates between anemic and normal livers, observed in the present study, might be attributed to the inhibition of DNA synthesis in the hepatocytes of anemic animals. 46,72 Moreover, iron deciency has been reported to cause the disorder of lipid metabolism in the liver, which caused the appearance of fat vacuoles in the hepatocytes, 73 as shown in anemic livers.…”
Section: Histological Analysis Of the Liversupporting
confidence: 93%
See 2 more Smart Citations
“…1B showed histopathological alterations in the liver, dilatation of both central and portal veins, distension and hemorrhage in the central vein, loss of the normal hepatocytes architecture, degenerated hepatocytes with pyknotic nuclei, hepatocyte vacuolization, dilation and activation of Kupffer cells of hepatic sinusoids, and the aggregation of lymphocytes. Similar results for normal and anemic livers were reported by He et al 46 The differences in hepatic sinusoids and hepatic plates between anemic and normal livers, observed in the present study, might be attributed to the inhibition of DNA synthesis in the hepatocytes of anemic animals. 46,72 Moreover, iron deciency has been reported to cause the disorder of lipid metabolism in the liver, which caused the appearance of fat vacuoles in the hepatocytes, 73 as shown in anemic livers.…”
Section: Histological Analysis Of the Liversupporting
confidence: 93%
“…Similar results for normal and anemic livers were reported by He et al 46 The differences in hepatic sinusoids and hepatic plates between anemic and normal livers, observed in the present study, might be attributed to the inhibition of DNA synthesis in the hepatocytes of anemic animals. 46,72 Moreover, iron deciency has been reported to cause the disorder of lipid metabolism in the liver, which caused the appearance of fat vacuoles in the hepatocytes, 73 as shown in anemic livers. Liver cells from G3, which were fed inulin free-yogurt, showed that the hepatocytes were partially complete, the nuclei were large and roundish, and there were hardly any fat vacuoles in the hepatocytes; however, the liver plates were slightly dilated (Fig.…”
Section: Histological Analysis Of the Liversupporting
confidence: 93%
See 1 more Smart Citation
“…To overcome ID, many different therapies are available, but none is side effects free; therefore, the scientific community is challenged to find more effective strategies that are less likely to cause side effects. To this line, important findings could come from animal models especially in the case of chronic intestinal inflammation and its related complications thanks to their ability to better resemble the human pathology [192][193][194].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Auricularia auricularia complexes induced anti-inflammatory and antioxidant effects while improving blood parameters in a rat model of anemia [175]. He et al obtained the same positive results with oligosaccharides derived from agar and chelated with iron ions [194]. Aspergillus oryzae contains huge amounts of iron and was studied in comparison with FeSO 4 .…”
Section: Superfoods As Nutritional Strategies For Iron Level Replenismentioning
confidence: 90%